Learning with Abductive-Pictorial Strategy for Improving Mathematical Proofing Ability of Prospective Mathematics Teachers - Ahmad Muzaki; YAYA S KUSUMAH; JOZUA SABANDAR (International Journal of Science and Applied Science: Conference Series, 2017)
This study aims to improve the mathematical proofing ability of prospective mathematics teachers in IKIP Mataram using Abductive - Pictorial Strategy (which will be abbreviated as APS). This study used an explanatory sequential design, a combination of quantitative and qualitative methods in sequence. The first stage is done by quantitative method and the second stage with qualitative method. Quantitative method is used to obtain measurable data and qualitative method is used to explore the findings obtained from the quantitative stage. This research considers the Prior Mathematical Knowledge (PMK) factor of prospective teacher. The results showed that the improvement of students' mathematical proofing ability in high, medium, and low PMK categories with APS better than Conventional Learning (CL). The mean improvement of students' mathematical proofing ability in high PMK category which got learning with APS and PK included in medium category. The mean improvement of students' mathematical proofing ability in medium PMK category with APS included in medium category, with CL included in low category. The mean improvement of students' mathematical proofing ability in the low PMK category with APS and CL included in low category.